Costs of minor bleeds in atrial fibrillation patients using a non-vitamin K antagonist oral anticoagulant. (2nd September 2021) - Mitrovic, Darko; Plomp, Marlies; Folkeringa, Richard; Veeger, Nic; Feenstra, Talitha; van Roon, Eric
Abstract: Background: A very common side effect of non-vitamin K antagonist oral anticoagulant (NOAC) is (minor) bleeding. Data about impact and costs of minor bleeds in NOAC therapy is still limited or not present in current literature. In this patient orientated study, we aim to provide an estimate of the costs of minor bleeds in patients with atrial fibrillation (AF) treated with a NOAC. Methods: A retrospective observational cohort study was conducted. Patients with AF and on NOAC therapy were included. Data was obtained by questionnaires and information from electronic patient records. Reference prices were used to calculate the costs per patient. Furthermore, cost of minor bleeds per patient is compared with literature-based costs of minor and major bleeding. Results: 139 patients were included. A total of 94 minor bleed were reported by 71 patients. The sum of minor bleeding costs from societal perspective were €9, 851.49, or on average €70, 87 (95% CI €54, 37– €85, 68) per patient with AF. The biggest cost drivers were rectal and vaginal bleeds, epistaxis was most commonly reported. Conclusion: Total costs of minor bleeds from a societal perspective, in AF patients using NOACs, are non-trivial and exceed the costs presented in existing literature.